People with a mild intellectual disability: inclusive research lessons. (March 2023) - Kyriazis, Elias; Pomering, Alan; Marciano, Heather
In this paper, we present guidelines for researchers working with individuals with mild intellectual disability (MID) based on the challenges and learnings from our University of Wollongong (UOW) Community Engagement Grant (2010) project where we collaborated with representatives from the Disability Sector, Cancer Council NSW and the vulnerable community of people with MID to overcome the difficulties that they face in interpreting mainstream cancer prevention messaging and take ownership of their skin cancer checking behaviour by using co-created resources that could be easily understood and acted upon by the target audience. As a result of our project, nearly 20% of our vulnerable population sample (employees of Greenacres, a disability employment provider) checked themselves for skin cancer spots for the first time after having been given a "What's that Spot?" book and accompanying resources (bathroom mirror stickers, hand held mirrors). The successful uptake can be directly attributed to the researchers putting aside their assumptions and overcoming the biases (conscious and unconscious) from their academic training to partner with the target population in a respectful manner and genuinely embrace the concept of inclusive research, ensuring that this overlooked and vulnerable group are afforded cancer prevention resources that work for them. This inclusive approach is evidenced by the co-creation of our "thumbs up scale" to overcome the limitations of traditional Likert scale use for our target population. Further, the generation of "trust" between researchers, participants and necessary carers should be at the forefront of all research methodology designs for those wishing to conduct research with members of the MID community.